Vistra Mewujudkan Sekolah Pencetak Wirausaha Negeri Atas Awan di SMK Negeri 1 Blado - Lutfah Barliana (Universitas PGRI Semarang, 2019)
Vocational High Schools are predicted as young generation printers who are ready to face the world of work and industry. In this case it means that SMK graduates are ready to work in industry or are entrepreneurs so that they can create their own jobs. However, in reality the last few years there have been various surveys conducted by statistical bodies which state that SMK graduates actually contribute the most to unemployment in Indonesia. Based on data from the Central Statistics Agency in February 2017 the number of unemployed people in Indonesia was 7.02 million with the highest percentage coming from vocational graduates at 9.84% (available at finance.detik.com accessed on April 1, 2019). The phenomenon is getting worse because in August 2017 the unemployment rate increased to 7.04 million. In August 2018 the unemployment rate of SMK graduates reached 11.25%. That number increased from February 2018 which had reached 8.92%. Actually this can be overcome by instilling an entrepreneurial spirit in students. If students are trained to be entrepreneurs at least even if students are not absorbed in working in the industry, they can still create their own business and the surrounding environment. For this reason researchers as principals at SMK Negeri 1 Blado carry out entrepreneurial tasks with a transformative visionary leadership style to form entrepreneurial printing schools. This best practice text aims to describe the implementation of transformative visionary leadership to form an entrepreneurial printing school along with the results, impacts, supporting factors, constraints and counter measures. The conclusions of this best practice script are (1) transformative visionary leadership to form entrepreneurial printing schools implemented by translating visionary ideas into factual reality, working together with all school members and the community which then proceed with the preparation and implementation of the program. The implementation of the entrepreneurship printing school program emphasizes three activities namely, entrepreneurship printing school worshop, entrepreneurship training, and industry visits to foster interest and talent of students in entrepreneurship and (2) the results of the application of transformative visionary leadership to form entrepreneurship printing schools are as many as 35 students of State Vocational Schools 1 Blado joined the program. One student managed to get a turnover of over five million rupiah over three months and had the opportunity to showcase his products at the 2019 national entrepreneurship exhibition. The obstacle factor in this program is the limited internet signal in the Blado region. The supporting factors of this program are support from the government and the development of information and communication technology. Follow-up from this program is that it will continue to be implemented in the second half of 2019 to encourage students to be more active in practicing their entrepreneurial abilities.